Lewis A Glycans Are Present on Proteins Involved in Cell Wall Biosynthesis and Appear Evolutionarily Conserved Among Natural Arabidopsis thaliana Accessions - Beihammer, Gernot; Maresch, Daniel; Altmann, Friedrich; Van Damme, Els J. M.; Strasser, Richard (Frontiers in Plant Science, 2021)
N-glycosylation is a highly abundant protein modification present in all domains of life. Terminal sugar residues on complex-type N-glycans mediate various crucial biological processes in mammals such as cell-cell recognition or protein-ligand interactions. In plants, the Lewis A trisaccharide constitutes the only known outer-chain elongation of complex N-glycans. Lewis A containing complex N-glycans appear evolutionary conserved, having been identified in all plant species analyzed so far. Despite their ubiquitous occurrence, the biological function of this complex N-glycan modification is currently unknown. Here, we report the identification of Lewis A bearing glycoproteins from three different plant species: Arabidopsis thaliana, Nicotiana benthamiana and Oryza sativa. Affinity purification via the JIM84 antibody, directed against Lewis A structures on complex plant N-glycans, was used to enrich Lewis A bearing glycoproteins, which were subsequently identified via nano-LC-MS. Selected identified proteins were recombinantly expressed and the presence of Lewis A confirmed via immunoblotting and site-specific N-glycan analysis. While the proteins identified in O. sativa are associated with diverse functions, proteins from A. thaliana and N. benthamiana are mainly involved in cell wall biosynthesis. However, a Lewis A-deficient mutant line of A. thaliana showed no change in abundance of cell wall constituents such as cellulose or lignin. Furthermore, we investigated the presence of Lewis A structures in selected accessions from the 1001 genome database containing amino acid variations in the enzymes required for Lewis A biosynthesis. Besides one relict line showing no detectable levels of Lewis A, the modification was present in all other tested accessions. The data provided here comprises the so far first attempt at identifying Lewis A bearing glycoproteins across different species and will help to shed more light on the role of Lewis A structures in plants.